Teachersâ€™ Teaching Methodologies and Attitudes as Correlate of Pupilsâ€™ Learning Outcomes in Surulere Local Government, Lagos State - Omotuyole, Christy Owolemi (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
Effective teaching at any stage in education particularly at the primary school level is to equip learners with life skills and bring out desired positive learning outcomes. Learning outcomes of pupils is very important because it showcases learnersâ€™ level of achievement. Hence, effective teaching at the primary school level becomes highly imperative. Despite this, empirical evidence has revealed that pupils are found to have poor learning outcomes. This disheartening situation has prompted numerous scholars to examine factors that could be responsible for this consistence poor performance. Among the factor were teachersâ€™ characteristics, school climate, lack of instructional materials, teachersâ€™ content knowledge, teaching motivation among others. However, much research attention has not been directed to the issue of teachersâ€™ teaching methodologies and attitudes. Hence, this study examined teachersâ€™ teaching methodologies and attitudes as correlate of pupilsâ€™ learning outcomes in Surulere Local Government, Lagos State. Two hypotheses were formulated and tested. Descriptive survey research design of the correlational type was used for the study. Simple random sampling technique was used to select eighty (80) teachers and pupils respectively. Three validated self-designed instruments were used to collect data for the study. The first instrument was titled â€œPrimary Schoolsâ€™ Teachersâ€™ Attitude Questionnaire (PSTAQ)â€ (0.77). The second instrument was titled â€œObservational Schedule for Primary Schoolsâ€™ Teachersâ€™ Teaching Methodologies (OSPSTTM)â€ (0.81). The third instrument was titled â€œPrimary Schoolsâ€™ Pupilsâ€™ Achievement Test (PSPAT)â€ (0.89). Data collected were analysed using inferential statistics of Pearson Product Moment Correlation (PPMC) for the hypotheses tested at 0.05 level of significance. Findings from the study revealed that a positive significant relationship exists between primary schoolsâ€™ teachersâ€™ attitudes and pupilsâ€™ learning outcomes (r = .100; N = 80; p<0.05) and a positive significant relationship exists between teachersâ€™ teaching methodologies and pupilsâ€™ learning outcomes (r = .120; N = 80; p<0.05). Hence, it was recommended that the federal government of Nigeria and private schoolsâ€™ owners should ensure prompt payment of teachersâ€™ salaries to enhance teachersâ€™ attitudes and that trainings and seminars should be organised for teachers on how to identify methods of teaching that best suit each topic as specified in the curriculum. Keywords: Teachers; Attitudes; Teaching Methodologies; Pupilsâ€™ Learning Outcomes